Student Creativity in Digital Learning: A Review of School Self-Confidence and Utilization - Mawar Izzati Khairuna; In In Supianti; Nenden Mutiara Sari (SJME (Supremum Journal of Mathematics Education), 2026)
Creativity is a crucial 21st-century skill, yet students' mathematical creativity remains relatively low. This research aims to develop mathematics learning materials based on the Pijar Sekolah Learning Management System (LMS) that are interactive, contextual, and problem-based to foster creativity by considering self-confidence. The Research and Development (R&D) method using the ADDIE model was employed. The sample consisted of two classes at a vocational school in Bandung. Data were collected via questionnaires, interviews, and observations, then analyzed using Aiken’s V, Cronbach’s Alpha, Two-Way ANOVA, and Pearson correlation. Results showed the materials are valid (Aiken’s V = 0.738) and reliable (Alpha = 0.945). Two-Way ANOVA revealed that the LMS method significantly improves creativity specifically for students with high self-confidence (p = 0.004), although it showed no significant difference for the overall group (p = 0.905). A significant positive correlation between self-confidence and creativity was found only in the experimental class (r = 0.478, p = 0.021). These findings emphasize that digital platforms optimize creativity when balanced with high student self-confidence.